A longitudinal assessment of the road to mental readiness training among municipal police. Issue 6 (2nd November 2018) - Carleton, R. Nicholas; Korol, Stephanie; Mason, Julia E.; Hozempa, Kadie; Anderson, Gregory S.; Jones, Nicholas A.; Dobson, Keith S.; Szeto, Andrew; Bailey, Suzanne
Abstract: Police agencies increasingly implement training programs to protect mental health. The Road to Mental Readiness (R2MR) program was designed by the Canadian military to increase mental health resilience. A version of R2MR was adapted for municipal police by the Mental Health Commission of Canada (MHCC). The current research was designed to assess the R2MR program, as adapted and delivered by the MHCC, in a municipal police sample. Participants were 147 Canadian police agency employees (57% women) who received a single R2MR training session. Participants completed pre- and post-training self-report questionnaires, and follow-ups at 6 and 12 months. The questionnaires assessed mental health symptoms, work engagement, resiliency, mental health knowledge, and stigma. Multilevel modeling analyses assessed for within-participant changes over time. The results were consistent with other single session interventions; specifically, there were no significant changes in mental health symptoms, resilience, or work engagement ( p > .05). There were small, but significant ( p < .05), reductions in stigma at post-training that may facilitate help-seeking among police; relatedly, in open-ended response fields, participants commonly described the training as helpful for changing attitudes and improving communication. More engagement with the material may produce larger, sustained gains, but more published research is critically needed.